O trabalho do agente comunitário de saúde: a voz dos gerentes de unidades de saúde da família - Menegussi, Juliana Morais (2014)
Family health program is founded on the strategy of reorienting the primary care model. This health care model marks the entry of an important professional in the Unified Health System (Sistema Único de Saúde - SUS), the Community Health Agent (Agente Comunitário de Saúde - ACS). The work of an ACS within a health unit team is very intense, given the tasks that are assigned to this professional. Therefore, there are inside the family health units professionals named managers, who have as one of his/her attributions the task of monitoring the activities performed by the ACS. Thus, since the managers are in daily touch with the community health agents, has emerged the motivation to understand the point of view of these professionals about the ACS. This study aims at understanding the point of view of managers (nurses, dentists, and doctors) about the work performed by the ACS within the family health units in the Regional Administration of Health (Administração Regional de Saúde - ARES) Cidade Aracy, located in the city of São Carlos SP. We adopted the qualitative analysis method, along with the application of semi-structured interviews and thematic analysis to form four categories: (i) comprehension of the work performed by community health agent; (ii) the ACS and his/her managers; (iii) the challenges of the management activities; and (iv) ACS: challenged of a professional category. The results of this study provide a better understanding of the managers point of view about the ACS, as well as it propose structural changes in order to allow to this professional exercising better their activities. This study also highlights the importance of the support and continuing education to the strengthening of the managers, so that this professional can better support the ACS work.